Draft Genome Sequences of Two Extensively Drug-Resistant Strains of Acinetobacter baumannii Isolated from Clinical Samples in Pakistan - Lomonaco, Sara (Microbiol Resour Announc, 2020)
Infections in immunocompromised patients that are caused by extensively drug-resistant (XDR) Acinetobacter baumannii strains have been increasingly reported worldwide. In particular, carbapenem-resistant A. baumannii strains are a prominent cause of health care-associated infections. Here, we report draft genome assemblies for two clinical XDR A. baumannii isolates obtained from hospitalized patients in Pakistan.